UnderApp: A System For Remote Monitoring Of Landslides Based On Wireless Underground Sensor Networks - Ferreira, Creyton B. de M.; Peixoto, Viviane F.; Brito, Jorge Augusto G. de; Monteiro, André Felipe de A.; Assis, Laura Silva de; Henriques, Felipe da R. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2019)
Every year several landslides are observed in Brazil, causing a major impact on the population which lives in risk areas. These events are permanent concerns for the local population, and also for the authorities responsible for monitoring the risk areas. This work presents UnderApp, a system for remote monitoring of landslides based on a Wireless Underground Sensor Network (WUSN). The sensor network is responsible to collect data in real time about rainfall and soil moisture, which are the main metrics for predicting the eminence of landslides. Then, the collected data is stored in a Web Server and sent to an App designed for smartphones to provide the data visualization by the local population and public authorities. A prototype was implemented and initial tests were performed to ratify the feasibility of the data collection and storage. Moreover, the App interface and its main features are presented as well.